Pemanfaatan Limbah Kelapa Sawit untuk Pembangkit Listrik di PT. X - M Abdul Aziz; Saleh Al Amin; Andi Arif Setiawan; Yudi Irwansi (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
The use of palm oil waste as boiler fuel is one of the innovative solutions in supporting the use of renewable energy while reducing the environmental impact of palm oil industry waste. Waste such as palm shells, mesocarp fibers, and empty oil palm bunches have high energy potential through direct combustion and other thermal technologies. This study aims to evaluate the potential use of palm oil waste as boiler fuel based on its calorific value, combustion efficiency, and environmental impact. The methods used include analysis of the physical and chemical characteristics of waste, boiler performance tests, and exhaust gas emission evaluation. The results show that palm oil waste has a high calorific value (15–20 MJ/kg), which makes it an efficient alternative fuel. In addition, the use of this waste is able to reduce dependence on fossil fuels while minimizing carbon emissions, thereby supporting the greenhouse gas emission reduction target. From an operational perspective, the use of palm oil waste in industrial boilers can increase combustion efficiency by up to 75–85%, depending on fuel conditions and boiler design. This makes palm oil waste not only economically valuable, but also strategic in supporting the transition to clean energy. Another advantage is that waste management becomes more targeted, because solid waste that is usually only an environmental burden can be reused as an energy source. However, some of the challenges that need to be considered include relatively high ash levels, the potential for corrosion in boiler equipment, and the need for emission control technology to comply with environmental standards. With the right mitigation strategy, palm oil waste can be processed into sustainable and environmentally friendly energy.